2021
DOI: 10.1093/jas/skab121
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber in a low-protein diet during gestation affects nitrogen excretion in primiparous gilts, with possible influences from the gut microbiota

Abstract: We investigated the effects of dietary fiber (DF) supplementation in normal or low crude protein (CP) diets on reproductive performance and nitrogen (N) utilization in primiparous gilts. In total, 77 Landrace × Yorkshire (LY) pregnant gilts were randomly allocated to four dietary treatments in a 2 × 2 factorial design. The groups comprised 1) equal intake of normal CP (12.82% and 0.61% total lysine), 2) low CP (10.53% and 0.61% total lysine), and 3) with or 4) without DF supplementation (cellulose, inulin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…In other studies, the combined supplementation of inulin and cellulose to increase both dietary SF and ISF contents had positive effects on ovarian follicular development in gilts [ 6 , 7 ] and litter size [ 8 ] in gestating sows. The current findings revealed that DF addition to both normal and low CP diets did not negatively affect the ADG of gestating sows, which is consistent with previous research using pectin, inulin, and cellulose as DF [ 4 ]. However, the ADG during days 91 to 110 of gestation was not affected by DF supplementation in sows fed the low CP diet but was increased by DF in gestating sows fed the low CP, indicative of the effect of DF and CP levels on the nutrient utilization of late gestating sows.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In other studies, the combined supplementation of inulin and cellulose to increase both dietary SF and ISF contents had positive effects on ovarian follicular development in gilts [ 6 , 7 ] and litter size [ 8 ] in gestating sows. The current findings revealed that DF addition to both normal and low CP diets did not negatively affect the ADG of gestating sows, which is consistent with previous research using pectin, inulin, and cellulose as DF [ 4 ]. However, the ADG during days 91 to 110 of gestation was not affected by DF supplementation in sows fed the low CP diet but was increased by DF in gestating sows fed the low CP, indicative of the effect of DF and CP levels on the nutrient utilization of late gestating sows.…”
Section: Discussionsupporting
confidence: 92%
“…Gestating sows were moved to stainless-steel metabolism crates to measure their nitrogen balance, as previously described [ 4 , 12 ]. There were two nitrogen balance trials conducted on days 30 to 38 and 90 to 98 of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary high CP level would increase the excretion of excessive nitrogen, reduce the efficiency of nitrogen utilization, and damage gut health by more protein fermentation in the hindgut ( 1 ). Many studies have shown that the reduction of dietary CP levels could effectively reduce the fecal and/or urinary nitrogen excretion in growing pigs ( 23 ), finishing pigs ( 13 ), primiparous gilts ( 24 ), as well as growing goats ( 25 ), and decrease blood urea nitrogen concentration in weaned piglets ( 26 ) and mice ( 27 ). Moreover, lowering dietary CP levels significantly reduced nitrogen consumption without negative consequences on growth performance in growing bulls ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiota were collected from each pen at day 28 and used in in vitro fermentation trials, conducted as previously described, but with minor modifications [ 14 ]. Briefly, feces were rectally collected, placed in plastic bags, anaerobically preserved in a foam box filled with ice, and transferred to the laboratory within 2 h. Feces (~70 g) were weighed and mixed with 0.9% sterile saline at 1:5 (g/mL).…”
Section: Methodsmentioning
confidence: 99%